Supplementation With Spirulina platensis Improves Tracheal Reactivity in Wistar Rats by Modulating Inflammation and Oxidative Stress - Brito, Aline de F.; Silva, Alexandre S.; de Souza, Alesandra A.; Ferreira, Paula B.; Souza, Iara L. L. de; Araujo, Layanne C. da C.; da Silva, Bagnólia A. (Frontiers in Pharmacology, 2022)
Spirulina platensis has shown effectiveness in the treatment of allergic rhinitis in rats, but its action in tracheal reactivity or on markers of relaxation and antioxidant profile has not yet been possible to determine. In this paper, the animals were divided into the groups sedentary (SG) and supplemented with S. platensis at doses of 50 (SG50), 150 (SG150), and 500 mg/kg (SG500). We constructed cumulative concentration-response curves and prostanoid pathways for the trachea. We also evaluated nitrite levels, lipid peroxidation, and antioxidant activity through biochemical analysis. For contractile reactivity, only SG500(pCE50 = 5.2±0.06 vs. pCE50 = 5.5±0.03, 5.5±0.06 and 5.7±0.06) showed reduction in carbachol contractile potency. Indomethacin caused a higher contractile response to carbachol in SG150 and SG500. For relaxation, curves for SG150(pCE50 = 5.0±0.05 vs. 4.5±0.02) and SG500(pD2 = 7:3±0:02 vs. 4.5±0.02) were shifted to the left, more so in SG500. We observed an increase in nitrite in the trachea only with supplementation of 500mg/kg (54.0±8.0µM), also when compared to SG50(37.0±10.0 µM) and SG150(38.0±7.0µM). We observed a decrease in lipid peroxidation in the plasma and an increase in oxidation inhibition for the trachea and lung in SG150 and SG500, suggesting enhanced antioxidant activity. S. platensis (150/500 mg/kg) decreased the contractile response and increased relaxation by increasing antioxidant activity and nitrite levels and modulating the inflammatory response.